Peningkatan Kemampuan Literasi Anak Usia 5–6 Tahun melalui Permainan Detektif Huruf dan Warna - Heri Hidayat; Fadilla Ayuninngtyas; Nisva Agnireven Waga; Siti Aulia Lahay; Najma Aliyjah (Program Studi Pendidikan Guru PAUD FKIP Universitas Mulawarman, 2026)
This study aims to determine the effect of the “Letter and Color Detective” educational game on the literacy development of children aged 5–6 years. The research method used was a quantitative study with a one-group design. The subjects in this study were children aged 5–6 years at the Uwais Al-Qarni Tutoring Center in Bandung. Data collection was conducted through observation, testing, and documentation, and the data were analyzed using descriptive statistics. The results of this study indicate that the implementation of the “Letter and Color Detective” educational game has a significant effect on the literacy development of children aged 5–6 years, as evidenced by the data: a pretest score of 17.25 (71.88%) and a posttest score that increased to 22.5 (93.75%). This increase in the percentage indicates that the “Color and Letter Detective” game is effective in improving the literacy skills of young children. Thus, the “Color and Letter Detective” game has a significant effect on the literacy development of children aged 5–6 years.